2022
DOI: 10.1155/2022/4717014
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Digestibility Coefficients of Black Soldier Fly (Hermetia illucens), Yellow Mealworm (Tenebrio molitor), and Blue Bottle Fly (Calliphora vicina) Insects for Juvenile African Catfish Hybrids (Clarias gariepinus × Heterobranchus longifilis)

Abstract: A digestibility trial was conducted with African catfish hybrid juveniles in order to determine the apparent digestibility coefficients (ADCs) of different nutrients. The experimental diets contained defatted black soldier fly (BSL), yellow mealworm (MW), or fully fat blue bottle fly (BBF) meals, in a 70 : 30 ratio between the control diet and the tested insect meals. The indirect method for the digestibility study was performed using 0.1% yttrium oxide as an inert marker. Fish juveniles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
3
5
0
Order By: Relevance
“…The decreasing tendency observed in our case in the growth performance of African catfish as the replacement level of FM with M meals increased could be associated with the lower palatability or poor digestibility of insects compared to FM. This is in line with previous findings presented by Sandor et al [ 49 ], when apparent digestibility coefficients (ADC) were calculated. In that study, low ADC amino acid was calculated for M meal fed to African catfish.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decreasing tendency observed in our case in the growth performance of African catfish as the replacement level of FM with M meals increased could be associated with the lower palatability or poor digestibility of insects compared to FM. This is in line with previous findings presented by Sandor et al [ 49 ], when apparent digestibility coefficients (ADC) were calculated. In that study, low ADC amino acid was calculated for M meal fed to African catfish.…”
Section: Discussionsupporting
confidence: 93%
“…In diet M50, 100 g of FM was replaced with mealworm meal (M); in diet M100, 200 g of FM was replaced with M; in diet B50, 100 g of FM was replaced with black soldier fly meal (B); in diet B100, 200 g of FM was replaced with B; in diet BM50, 100 g of FM was replaced with a 1:1 combination of M and B; and in diet BM100, 200 g of FM was replaced with a 1:1 combination of M and B. The chemical composition of insects used in feeds is similar to data presented by Sandor et al [ 49 ]. The experimental diets were set to be iso-nitrogenous and iso-energetic ( Table 1 ).…”
Section: Methodssupporting
confidence: 71%
“…The feed ingredients (Table 1) were thoroughly mixed to form a homogenous blend, moistened with water (200 mL kg −1 ) then extruded with a single screw extruder (Abrazive, Hungary) to produce 6 mm sinking pellets, which were dried in an oven at 55°C (Pol-Eko, Wodzislaw Slaski, Poland). The chemical compositions of insects used in feeds are similar to data presented by Sándor et al [17].…”
Section: Methodssupporting
confidence: 83%
“…Chitin has both beneficial functions (e.g., prebiotic effects) and putative negative effects on digestibility [47]. However, chitin is a relatively small component of most insects; e.g., Sándor et al [50] found its proportions to be 9.6 and 5.5% in dry matter in BSF and mealworm meal, respectively. On the other hand, some animal species have chitinases in their gastrointestinal tracts.…”
Section: Edible Insects Farming Products and Nutritional Valuementioning
confidence: 99%